A study on user's satisfaction of physical indoor environment towards building design at library / Muhammad Ridhzuan Muhammad Naim and Nur Fadhilah Bahardin - Muhammad Naim, Muhammad Ridhzuan; Bahardin, Nur Fadhilah (2018)
Physical environment in a building could give an impact to the user physically, mentally, and social wellbeing especially indoor environment. A good environment has been recognized to give a positive and negative impact on the user state-of-mind as well as their routine productivity. The aim of the study was to find the key factor of indoor physical environment to produce a conducive physical indoor environment for public building such as library. Data collection based on the methodology used was from quantitative method and the sample of case study chosen were library at UiTM Seri Iskandar and Tapah campus. Result analysis from extensive literature had shown that layout arrangement is the most key factor that affects the indoor environment at the library.